Graphene oxide-based nanomaterial interaction with human breast cancer cells - Ribeiro, Beatriz F. M.; Souza, Marcelo M.; Fernandes, Daniela S. [UNESP]; Carmo, Devaney R. do [UNESP]; Machado-Santelli, Glaucia M. (Wiley-Blackwell, 2019)
Graphene and graphene-based nanomaterials have great potential for various biomedical applications due to their unique physicochemical properties. However, how graphene-based nanomaterials interact with biological systems has not been thoroughly studied. This study shows that 24, 48, and 72 hr exposure of 2.4 mu g/cm(2) of graphene oxide (GOX) and GOX modified with DAB-AM-16 and PAMAM dendrimers (GOXD and GOXP, respectively) did not exhibit toxicity to MCF-7 cells. However, higher graphene concentrations, such as 24 and 48 mu g/cm(2), induced low cytotoxic effects. The GOX, GOXD, and GOXP particles have a strong affinity with the cellular membrane. Cells that internalized the nanomaterials presented morphological alterations and modifications in the organization of microfilaments and microtubules compared with control cells. Then, cells were treated with 24 mu g/cm(2) of GOX, GOXD or GOXP for 24 hr and recovered for an additional period of 24 hr in normal medium. Nanoparticles remained in the cytoplasm of some cells, apparently with no effect on cellular morphology, being consistent with the data found in the cell proliferation experiment, which showed that the cells remained alive up to 72 hr.
Keywords: cell morphology; cell proliferation; Dendrimer; Graphene oxide; nano-bio interaction